Experimental and numerical investigations on slim floor beams exposed to fire. (October 2021) - Alam, Naveed; Nadjai, Ali; Hanus, Francois; Kahanji, Charles; Vassart, Olivier
Abstract: Slim floor systems possess favourable thermal and thermo-mechanical behaviour in comparison with the traditional steel-concrete composite beams. Despite a recent surge in their usage in the construction sector, there is limited research on their performance at elevated temperatures. Due to limited investigations, there is a lack of fire design guidance for slim floor beams in major structural design codes. This study addresses the response of slim floor systems at elevated temperatures through experimental and analytical investigations. The experimental work consists of fire tests to study the thermo-mechanical response of SFBs in standard fire conditions. In addition to their thermo-mechanical response in fire, the efficiency of the rebars as an aid to enhance their fire resistance being an alternative to fire protection materials is also investigated. The test results show that the fire resistance of slim floor beams is significantly higher than the traditional steel-concrete composite beams due to the thermal gradient resulting from the concrete encasement. Further, the presence of longitudinal steel rebars enhances the fire resistance of SFBs significantly as they add to the flexural resistance of SFBs. During the tests, additional fire resistance of 79 min was achieved by the aid of steel rebars, a useful alternative to the fire protection materials which have been found to be toxic to the environment. Keeping in view the useful contribution of the steel rebars, a sensitive study was conducted using the finite element modelling to analyse the influence of their size and positioning on the fire resistance of the slim floor beams. Finite element modelling was later used to conduct a parametric study to analyse the influence of the degree of utilization on the response of slim floor beams exposed to standard fire. Degree of utilization represents the ratio between the applied load during a fire limit state and the capacity of the structural member at the ambient temperatures. The results from the parametric study were used to develop a simple design methodology by relating the degree of utilization and the average critical temperatures. Due to lack of fire design guidance in Eurocode 4, engineers usually use the design guidance proposed in Eurocode 3 which produces conservative results if applied to perform the fire design of slim floor beams as they have been developed for steel and traditional composite beams. The proposed methodology during this study is similar to that available in the Eurocodes for steel and composite beams but is developed specifically for the fire design of slim floor beams. Highlights: Experimental Investigations of Slim Floor Beams. Fire Design methods of Slim Floor Beams. Use of steel rebars to enhance fire resistance of Slim Floor Beams. Standard fire tests.